Enantioselective Michael Addition of Dimethyl Malonate to (E)-β- Nitrostyrenes Catalyzed by Cinchona Alkaloids Under Solvent-Free Condition - Fringuelli, Francesco; Castrica, Luca; Pizzo, Ferdinando; Vaccaro, Luigi (Letters in Organic Chemistry, 2008)
Under solvent-free condition the addition of dimethyl malonate (1) to (E)-β-nitrostyrenes 2a-j proceeds smoothly in the presence of 2.5 mol% of 6'-hydroxy cinchonine (QD-OH) and equimolar amounts of reagents at 30 °C. The corresponding products 3a-j are obtained with satisfactory enantiomeric excesses (68-88%) and high yields (70- 92%).
Keywords: Michael addition